2020
DOI: 10.1177/0734242x19900654
|View full text |Cite
|
Sign up to set email alerts
|

Anti-littering in developing countries: Motivating the people of Jordan

Abstract: Littering in developing countries remains a problem that has not been overcome, and past research based on a trial-and-error approach has not solved the problem. In this study, a questionnaire was constructed and distributed to the people of Jordan. People were asked to indicate what motivates them to use the litter bins. The motivators were divided into intrinsic motivators and extrinsic motivators. The responses to the questionnaire were statistically analysed according to the score for each motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Previously, scholars often associated littering behavior with motivational factors, knowledge, awareness. Moqbel, El-tah, and Haddad [8] in their study have suggested that combining intrinsic and extrinsic motivators in understanding anti-littering can improve the strategy. Mapotse and Mashiloane [9] have suggested that environmental education be applied to school students because it can increase students' awareness on littering.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previously, scholars often associated littering behavior with motivational factors, knowledge, awareness. Moqbel, El-tah, and Haddad [8] in their study have suggested that combining intrinsic and extrinsic motivators in understanding anti-littering can improve the strategy. Mapotse and Mashiloane [9] have suggested that environmental education be applied to school students because it can increase students' awareness on littering.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To find a lasting solution to the littering problem, it is important to understand the factors that motivate people to dump litters in the environment or in the bin [13]. Researchers [13] explored these motivating factors by conducting a survey that asked people to indicate what motivates them to drop litters in the bin. An analysis of the survey responses divided the motivators into intrinsic and extrinsic motivators.…”
Section: A Improving Children's Littering Behaviormentioning
confidence: 99%
“…Street litter mainly results from inappropriate disposal of waste by pedestrians and vehicle passengers, although some items fall off vehicles accidentally, for example unsecured loads or pieces of the vehicles themselves, and there may be leakage from poorly designed/managed waste receptacles (Schultz et al 2013 ). There are numerous studies of why people litter, with both intrinsic and extrinsic factors affecting the propensity to litter (e.g., Williams et al 1997 ; Torgler et al 2012 ; Ojedokun 2013 ; Moqbel et al 2020 ). However, surprisingly little appears to have been reported on how litter loads correlate with human activity.…”
Section: Introductionmentioning
confidence: 99%
“…The gradual easing of restrictions over the following months provided a unique opportunity to assess how litter loads changed as human movement increased. Despite many years of education and awareness campaigns, street litter remains a significant source of mismanaged solid waste, particularly in developing countries (Moqbel et al 2020 ), and is a major contributor to aquatic pollution in South Africa (Verster and Bouwman 2020 ; Weideman et al 2020a ). By improving our understanding of how litter loads vary in response to human activity, we can inform mitigation measures aimed at stopping the release of litter into the natural environment.…”
Section: Introductionmentioning
confidence: 99%